2007
DOI: 10.1038/nm1486
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of siRNA delivery and silencing in tumors

Abstract: With the increased potential of RNA interference (RNAi) as a therapeutic strategy, new noninvasive methods for detection of siRNA delivery and silencing are urgently needed. Here we describe the development of dual-purpose probes for in vivo transfer of siRNA and the simultaneous imaging of its accumulation in tumors by high-resolution magnetic resonance imaging (MRI) and near-infrared in vivo optical imaging (NIRF). These probes consisted of magnetic nanoparticles labeled with a near-infrared dye and covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
537
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(549 citation statements)
references
References 35 publications
4
537
0
3
Order By: Relevance
“…The conjugation of oligonucleotides to carrier nanoparticles can be achieved using electrostatic interactions with cationic polymers or by covalent attachment either to the polymer [83] or directly to the nanoparticle [84]. A number of cationic polymers (e.g.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The conjugation of oligonucleotides to carrier nanoparticles can be achieved using electrostatic interactions with cationic polymers or by covalent attachment either to the polymer [83] or directly to the nanoparticle [84]. A number of cationic polymers (e.g.…”
Section: Review Articlementioning
confidence: 99%
“…Medarova et al [83] used a different strategy to deliver siRNA with IONPs based on the use of multimodal IONPs. First, IONPs were coated with a dextran polymer layer bearing amine groups.…”
Section: Review Articlementioning
confidence: 99%
“…With this, Moore and her colleagues thought they had a particle that could target and image delivery to tumour cells in vivo. But the imaging showed that the nanoparticle went to the liver and kidneys, and was present in other organs as well 5 .…”
Section: Local Deliverymentioning
confidence: 99%
“…nanosized structures made by an inorganic material (e.g. silica, gold, iron oxide, quantum dots, carbon nanotubes, calcium phosphate), coated by polymeric layers and conjugated to siRNA through specific approaches including covalent binding, electrostatic absorption and encapsulation, depending on the material [17][18][19][20][21][22]. Compared to conventional transfection agents, nanoparticle-conjugated siRNAs have been shown to be less susceptible to degradation by nuclease activity, exhibit greater cellular uptake and higher siRNA effective concentration; which has accelerated siRNA delivery in this direction over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 REVIEW NANO TODAY 6 Despite the enormous efforts to develop NP based siRNA carriers, most of the studies have been performed in cell cultures, using reporter genes such as the green fluorescent protein or luciferase, allowing easy recording of the RNAi efficacy. Less abundant are studies employing pre-clinical animal models (mainly mouse) [18,28,31], or targeting biologically relevant genes, and very rare those reporting on clinical trials using inorganic nanoparticles [30,35]. In fact, there are no active clinical trials reporting the use of inorganic NPs to target any gene using siRNA delivery (see Table 2).…”
Section: Introductionmentioning
confidence: 99%